Methodology to Determine Ground Potential Rise in Multi-Grounded Neutral Distribution System with Distributed Generation - Yun, Sangwon; Jung, Jaesung (IEEE Power and Energy Society General Meeting, 2021)
In a multi-grounded neutral distribution system, the interconnection of distributed generation (DG) may affect the level of ground potential rise (GPR). However, the methodology for analyzing the GPR caused by integrating various DGs has not been investigated. This paper proposes a methodology to determine the level of GPR by interconnecting different types of DGs. For this purpose, an existing analysis methodology for GPR is introduced briefly. Then, a methodology to analyze GPR based on the type of DG is proposed. Finally, GPR with and without DG was analyzed to prove the necessity of the proposed methodology for accurate calculation of GPR.
Keywords: Accurate calculations; Distribution systems; Ground potential rise; Inverte-based distributed generation; Inverter-based; Multi-grounded neutral distribution system; Synchronoi-machine-based distributed generation; Synchronous machine; Ground Potential Rise; Inverter-Based Distributed Generation; Multi-Grounded Neutral Distribution System; Synchronous-Machine-Based Distributed Generation